Providing Long-term Sustainability to Capital Outlay Funding in Kansas - Kellen James Adams (Educational Considerations, 2024)
The purpose of this study was to provide insight into the challenges and limitations of the capital outlay fund across the range of the 286 school districts in the state of Kansas. The data and conclusions gleaned from the study conducted here are of importance for local governing bodies and state policymakers alike, as they look to provide for the long-term sustainability of the pupils of Kansas. The stark reality facing Kansas school districts and their respective school buildings is that, for many, the proverbial clock is ticking on their life expectancy. In some cases, buildings are simply living on borrowed time with failing critical systems and classroom environments that are not truly conducive to maximizing student learning. As the costs of maintaining and operating these buildings continue to rise, current statutory provisions mean less revenue is available for districts to use toward renovation, remodeling, replacement, or any other alternative that truly extends the life expectancy of a learning environment. The study was conducted by using the latest audited fiscal year (FY 2023) data to create three distinct fiscal profiles: 1) The current reality under the Kansas statutory limitations as they exist today; 2) A first alternative that provided for an increase to the statutory limit set on the mill rate for the capital outlay fund; and 3) A second alternative mirroring that of the first, while increasing the statutory cap even further. Each of these three fiscal profiles were then examined using common descriptive statistics to provide an analysis of implications across the state. The results of the study were clearly indicative of the need for legislative policy change if the state’s school districts want to make a lasting, positive impact upon their students’ physical learning environments. The current fiscal profile reveals that there is very little unused and accessible statutory authority or matching state aid because school districts are taxing and spending to current limits. Both alternative fiscal profiles revealed that a substantial amount of additional monies could be made available at relatively low political effort, with positive implications at the local level for taxpayers, and modest effect as well on the state’s coffers. While policy implications abound, a consideration of what the results in this study reveal is noteworthy as boards of education, as well as legislators, grapple with how to balance the needs of Kansas school districts and the taxpayers who provide the required financial resources. While the looming backlog of deferred maintenance should certainly bring attention to the level of concern present here, the true reality is the consequence of failing to address these issues for the pupils of Kansas and the impacts upon their educational success.
Keywords: Capital Outlay; Funding; Infrastructure